2001
DOI: 10.1177/009145090102800402
|View full text |Cite
|
Sign up to set email alerts
|

The History of Addiction/Recovery-Related Periodicals in America: Literature as Cultural/Professional Artifact

Abstract: Can significant changes in the addictions field be identified by examining its specialized literature? Are political, economic, and cultural changes surrounding addiction and its treatment mirrored in its literature? In this paper an addictions historian/author (William White) and an addictions librarian/information professional (Barbara Weiner) examine the past 150 years of addiction/recovery history by analyzing the literature of the field. Over 250 American journal, magazine, and newsletter titles were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…They noted the need for increased research on addiction literature using bibliometric methods and recognized the difficulties of using citation counts where the intended audiences of particular journals and articles were not scientists. Weiner and White studied addiction periodical literature from 1776-2001 in relation to its origins in social movements and medical and mutual aid societies [26]. West and Mcllwaine's 2002 study of citation counts to research published in the journal Addiction found no link between citation counts and peer ratings of quality [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They noted the need for increased research on addiction literature using bibliometric methods and recognized the difficulties of using citation counts where the intended audiences of particular journals and articles were not scientists. Weiner and White studied addiction periodical literature from 1776-2001 in relation to its origins in social movements and medical and mutual aid societies [26]. West and Mcllwaine's 2002 study of citation counts to research published in the journal Addiction found no link between citation counts and peer ratings of quality [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There was an explosion in publishing activity on recovery in addictions between 1960 and the early 1990s, which resulted mainly from the emergence of recovery as a cultural and political phenomenon seen in the proliferation of mutual-aid groups and the application of the AA "Twelve Steps" to a wide variety of human problems (Weiner & White, 2001). However, there are still a number of unresolved questions relating to recovery in addiction (Blomqvist & Cameron, 2002;Edwards & Lader, 1994;Moos 2003;Sobell et al, 2000;Tims et al, 2001).…”
Section: Narrative Identity In Recovery From Addiction Recovery From Addictionmentioning
confidence: 99%
“…Two such publications—Dr Robert Parrish's The Probe (Pennsylvania Sanitarium for Inebriates) (Fig. 2), and Dr H. H. Kane's Journal of Stimulants and Narcotics (De Quincey Home)—aspired to compete with the JI as the leading addiction medicine journal, but the JI survived as the primary publication focused on addiction treatment throughout the years it was published [7].…”
Section: The First Journal Of Addiction Medicinementioning
confidence: 99%
“…The founding of the Scientific Temperance Federation in 1906 and its publication of the Scientific Temperance Journal (Fig. 5) to compete with the AACI and the JI reflected that shift [7].…”
Section: The First Journal Of Addiction Medicinementioning
confidence: 99%
See 1 more Smart Citation